Studi Komparasi Strategi True Or False Dengan Crossword Puzzle Terhadap Hasil Belajar IPS Siswa Kelas V SDIT Nur Hidayah Surakarta Tahun Pelajaran 2015/2016 - Juliantika, Vira, Drs. Mulyadi Sri Kamulyan, M.Pd (2016)
The lack of adequate facilities and infrastructure, as well as the lack of creativity of teachers in managing learning is a problem that is often experienced teachers in the implementation of PAIKEM. The use of active learning strategies can help teachers to create PAIKEM. This research is aiming at: (1) differences in student learning outcomes of social science in the application of true or false strategy with a crossword puzzle at the 5^th grade student of SDIT Nur Hidayah Surakarta 2015/2016 academic year, (2) better between the applicability of true or false strategy with a crossword puzzle in learning outcome of social science at the 5^th grade student of SDIT Nur Hidayah Surakarta 2015/2016 academic year. This research is experiment quantitative. The subject of this research is 5^th grade B and 5^th grade D of SDIT Nur Hidayah Surakarta 2015/2016 academic year. The tehnique of collecting data is test and documentation. The tehnique of analizing data is t-test which doing pre-requisite test like homogeneity test and normality test first. Based on the data analysis about 5% degree's significance the result shows t_test>t_tabel is 3,802>1,998 which the average of the learning outcome at 5^th grade D is bigger than 5^th grade B, the result shows 83,030>80. The conclusion of this research is (1) there are differences in learning outcome of social science using true or false strategy and crossword puzzle strategy at the 5^th grade student of SDIT Nur Hidayah Surakarta 2015/2016 academic year, (2) crossword puzzle strategy better compared application with the true or false strategy auctioned in learning outcome of social science at the 5^th grade student of SDIT Nur Hidayah Surakarta 2015/2016 academic year. Keyword: learning outcome, crossword puzzle strategy, true or false strategy.